Віщунки в румунів Тімоку: колективний та індивідуальний фольклорний репертуар - Сорєску-Марінкович, А.-М. (Народна творчість та етнологія, 2011)
This paper is based on the field material recorded by the author between 2002 and 2009 in several Vlach villages of North-Eastern Serbia. The respondents narrate about the three Fates which visit the house of the newborn three nights after birth, both in the first person singular, from their own experience, and in the third person, reproducing the already existing texts which circulate within the community for generations. Analyzing all these texts, we try to answer the question whether the individual creations of the specialized interlocutor can also be transferred, sooner or later, to the community collective repertoire, whether the specialized interlocutors can act as factors of change in the community’s repertoire. Articolul se bazează pe materialele de teren înregistrate de autor între 2002 şi 2009 în câteva sate vlahe din nord-estul Serbiei. Respondenţii povestesc despre cele trei ursitoare care vizitează casa nou-născutului în cele trei nopţi de la naştere, atât la persoana I, din propria experienţă, cât şi la persoana a III-a, reproducând texte deja existente care circulă în interiorul comunităţii de generaţii. Analizând toate aceste texte, încercăm să răspundem la întrebarea dacă anumite creaţii individuale ale unui interlocutor specializat pot fi transferate, mai devreme sau mai târziu, în repertoriul colectiv al comunităţii, dacă interlocutori specializaţi pot acţiona în calitate de factori de schimb ai repertoriului comunităţii.